ANALISA PENINGKATAN MINAT TERHADAP PRODUK ASURANSI SYARIAH - Silpiah Jahra Nasution; Zainarti Zainarti (CV. ADIBA AISHA AMIRA, 2024)
This study aims to analyze the factors driving the increase in public interest in sharia insurance products. The approach used is a qualitative method with data collection techniques through interviews and document studies. The results show that public interest in sharia insurance is influenced by an understanding of sharia principles, trust in insurance institutions, service quality, and product innovation. In addition, promotional factors and the ease of the claim process also play an important role in increasing customer interest. These findings indicate that sharia insurance companies need to enhance sharia financial literacy and optimize digital-based marketing strategies. These efforts are expected to expand the customer base and strengthen public trust in sharia insurance products